Prognostic significance and gene co-expression network of CD16A and FGL2 in gliomas - Cao, Ziwen; Liu, Xing; Yan, Jun (Frontiers in Oncology, 2024)
IntroductionThe CD16A protein encoding gene FcγRIIIa (FCGR3A) and its potential ligand Fibrinogen-like protein 2 (FGL2) are involved in various cell physiological activities on the extracellular surface. Aberrant expression of these genes has been linked to tumorigenesis.MethodsTo assess the prognostic significance of FCGR3A and FGL2 transcription expression in glioma and explore their roles in glioma initiation and progression, we utilized multiple online databases, including TCGA, GEPIA, CGGA, cBioPortal, TISCH, LinkedOmics, Ivy Glioblastoma Atlas Project, and Human Protein Atlas.ResultsOur analysis revealed that FCGR3A and FGL2 expression was significantly correlated with clinical variables such as age, tumor type, WHO grade, histology, IDH-1 mutation, and 1p19q status. A strong correlation was also observed between the transcriptional expression levels of FCGR3A and FGL2. High expression of both genes predicted poor prognosis in primary and recurrent glioma patients, particularly those with lower grade gliomas. Cox regression analysis further confirmed that elevated expression of FCGR3A and FGL2 were independent prognostic factors for shorter overall survival in glioma patients. Gene co-expression network analysis suggested that FCGR3A, FGL2, and their co-expressed genes were involved in inflammatory activities and tumor-related signaling pathways. Additionally, tissue microarrays from glioma patients at Tiantan Hospital showed significantly higher FCGR3A protein expression in high-grade gliomas compared to low-grade gliomas.DiscussionIn conclusion, our findings suggest that FCGR3A and FGL2 could serve as promising prognostic biomarkers and potential therapeutic targets for glioma patients.